2014
DOI: 10.1016/j.bpj.2014.05.045
|View full text |Cite
|
Sign up to set email alerts
|

UNC-45B Chaperone: The Role of its Domains in the Interaction with the Myosin Motor Domain

Abstract: The proper folding of many proteins can only be achieved by interaction with molecular chaperones. The molecular chaperone UNC-45B is required for the folding of striated muscle myosin II. However, the precise mechanism by which it contributes to proper folding of the myosin head remains unclear. UNC-45B contains three domains: an N-terminal TPR domain known to bind Hsp90, a Central domain of unknown function, and a C-terminal UCS domain known to interact with the myosin head. Here we used fluorescence titrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…1c), we estimated the apparent K d of this effect at ∼2.2 μM. This value for the K d is in good agreement with recent fluorescence data from our laboratory [14,25].…”
Section: Resultssupporting
confidence: 90%
“…1c), we estimated the apparent K d of this effect at ∼2.2 μM. This value for the K d is in good agreement with recent fluorescence data from our laboratory [14,25].…”
Section: Resultssupporting
confidence: 90%
“…Binding curves were fit by using KaleidaGraph software (Synergy Software, PA). In the case of titrations using competition with A(pA) 19 , the relative increase in the fluorescence of the nucleic acid (ΔF) upon binding of DENV NS5 is defined as ΔF obs ϭ (F i Ϫ F 0 )/F 0 , where F i is the fluorescence of the nucleic acid solution at a given titration point, i, and F 0 is the initial fluorescence of the sample (29,(37)(38)(39). In the case of direct titrations of fluorescein-modified SLA, the relative fluorescence change is defined as F i /F 0 .…”
Section: Methodsmentioning
confidence: 99%
“…The binding constant was determined by using equation 5. In the competition assay, labeled A(pA) 19 (38). Experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…While invertebrates express one Unc-45 protein, vertebrates express two, Unc-45a that is present in general cell types and Unc-45b that is specifically expressed in striated muscle cells (453). Extensive biochemical and biophysical work has shown that Unc-45b binds to the myosin head domain via its central and UCS domains (72). Gain and loss of function experiments using in vitro and in vivo models demonstrated that while Unc-45a is critical for cell proliferation and fusion, Unc-45b is essential for myoblast fusion and sarcomeric organization (317, 453, 577, 606).…”
Section: Myosinmentioning
confidence: 99%